Effect of contact surface area on frictional behaviour of dry and saturated rock joints. (June 2020) - Pirzada, M.A.; Roshan, H.; Sun, H.; Oh, J.; Andersen, M.S.; Hedayat, A.; Bahaaddini, M.
Abstract: Frictional behaviour of joints/faults is of great importance in many geo-engineering applications across different scales. It is known that the joint surface roughness is one of the critical parameters controlling the frictional behaviour of rock joints. While nominal normal and shear stresses acting across the joint asperities are calculated based on overall shearing area, the actual normal and shear stresses can be much greater due to smaller actual contact area. The actual contact area on the other hand is known to be related to the joint surface roughness. In order to investigate the effect of contact area on the shear behaviour of rock joints, an extensive set of direct shear experiments at different normal stresses on dry and saturated shale, limestone and sandstone tensile joints were undertaken. To compare the frictional properties of natural and artificial samples, synthetic samples were also fabricated, and their frictional properties were evaluated. Results of this study revealed that the predominant parameter controlling the frictional strength is the actual contact area. While the common models in predicting the shear strength of rock joints were unable to fit the experimental data based on nominal contact area, the results based on actual contact area fit the measured values accurately. In addition, it was observed that when the actual contact area is considered, Mohr-Coulomb criterion is sufficient to fit the experimental data irrespective of the rock type, joint surface roughness or whether dry or saturated. This highlights that the Mohr-Coulomb criterion can appropriately predict the frictional strength if the actual contact area can be estimated. More importantly, the results showed that the surface roughness cannot dictate the shear behaviour of rock joints without considering the actual contact area. Highlights: Direct shear tests at different normal stresses on dry and saturated joints were undertaken. Experiment were carried out on natural and synthetic rock joints. The predominant parameter controlling the frictional behaviour is the actual contact area. Mohr-Coulomb criterion can predict the shear strength considering actual contact area.